Effectiveness of simple motor skills training (SMST) and complex motor skills training (CMST) in young boxing students (aged 13–14) from a rural school in Kazakhstan - Akhmetov, R.; Tolegenuly, N.; Yerofeyeva, R.; Balgimbekov, Sh.; Grigorkevich, A.; Imanbetov, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Boxing sport requires an effective selection of strategies, skills, and techniques. Mastering skills ranging from simple motor skills (SMS) to complex motor skills (CMS) requires dedicated training and engagement. This study was designed to assess the association between complex motor skills training (CMST), simple motor skill training (SMST), and technical performance effectiveness (STPE) among boxing students of Terekti Village Sports School in Kazakhstan. The study included 160 male students aged 13–14 from 8th and 9th grade. They were divided into two groups, each consisting of four teams, with 20 boxing students per team. The association between SMST and CMST was statistically significant (β = 0.313). CMST has a strong positive and statistically significant (p = 0.000) association with SMST (r = .620**). STPE has a strong positive association with SMST (r = 0.781**) and with CMST (r = 0.674**). Therefore, from the Pearson correlation analysis, we found that SMST, CMST, and STPE are all positively associated. The study findings showed that simple motor skills training (SMST) is positively associated with complex motor skills training (CMST). Both CMS and CMS are positively associated with students’ technical performance effectiveness (STPE).
Keywords: Boxing; Complex Motor Skills Training (CMST); Simple Motor Skills Training (SMST); Student Technical Performance Effectiveness (STPE); Kazakhstan